INVESTIGATION OF THE CAPABILITIES OF ARTIFICIAL NEURAL NETWORKS WHEN CLASSIFYING OBJECTS DYNAMIC FEATURES - Nikita V. Laptev; Olga M. Gerget; Vladislav V. Laptev; Dmitriy Yu. Kolpashchikov (Известия Томского политехнического университета: Промышленная кибернетика)
Image classification is a classic machine learning task. Deep neural networks are widely used in the field of object classification. However, the problem of analyzing objects with dynamically changing features remains relevant. To solve this problem, the authors propose using a long short-term memory networks. Unlike classical convolutional neural networks, the proposed network uses information about the sequence of images, thereby providing a higher classification accuracy of detected objects with dynamic features. In the study, the authors analyze the classification accuracy of smoke cloud detection in a forest using various machine learning methods.